2016
DOI: 10.3892/mmr.2016.5360
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characteristics of the testes-specific gene, Ccdc38, in mice

Abstract: Abstract. Distinguishing the testes-specific genes in different species may disclose key genes associated with testes-specific functions and provide sufficient information for the study and treatment of male infertility. A testes-specific gene, coiled-coil domain containing 38 (Ccdc38), was identified by screening UniGene libraries. Systematic bioinformatics analysis demonstrated that the CCDC38 protein was conserved in various mammalian species. It was determined that CCDC38 was exclusively expressed in teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…We performed a survey of the literature published on these 412 uPE1 proteins using various search engines and could find a publication reporting the location of TEX33 in the mouse male germ cell lineage . We also found publications reporting functional roles for CCDC38, CFAP70, CFAP58, and C3orf62 (further discussed in this study) in spermatogenesis, and for ANKDR45 in cell proliferation (Table ). The five latter proteins should no longer be considered as “uPE1” according to neXtProt criteria.…”
Section: Resultssupporting
confidence: 79%
“…We performed a survey of the literature published on these 412 uPE1 proteins using various search engines and could find a publication reporting the location of TEX33 in the mouse male germ cell lineage . We also found publications reporting functional roles for CCDC38, CFAP70, CFAP58, and C3orf62 (further discussed in this study) in spermatogenesis, and for ANKDR45 in cell proliferation (Table ). The five latter proteins should no longer be considered as “uPE1” according to neXtProt criteria.…”
Section: Resultssupporting
confidence: 79%
“…Ccdc38 is a testis specific expression gene (Lin et al, 2016), but its role during spermiogenesis has not been investigated yet. In order to study its role during spermiogenesis, we generated Ccdc38 -/mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…1A). CCDC38, reported as a testisspecific protein (Lin et al, 2016), was chosen first. Epitope-tagged CCDC42 and CCDC38 expressed in HEK293T cells followed by immunoprecipitation experiments demonstrated that CCDC38 was detected in anti-MYC immunoprecipitates from CCDC42 co-transfectants, but not from cells co-transfected with the control plasmid (Fig.…”
Section: Ccdc38 Interacts With Ccdc42mentioning
confidence: 99%